AGRICULTURAL DECISION-MAKING CONCERNING CROP SELECTION USING ANALYTIC HIERARCHY PROCESS (AHP) IN TRAKYA REGION OF TÜRKIYE - GAYTANCIOĞLU, Okan; YILMAZ, Fuat (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
The multitude of factors that can influence decision-making in agricultural production may have a negative impact on the outcome. Therefore, it is necessary to have access to information and a decision-making process that can facilitate the decision-making process. The Analytic Hierarchy Process (AHP) is a valuable decision-making methodology that can be applied not only in agricultural production but also in various other fields.This research evaluates four products using the AHP method based on criteria determined by 330 producers and specialists in an area with equal irrigation opportunities for each product.  The goal is to determine the most suitable products to plant in these areas. We found rice as the crop offering the highest profit levels. The AHP model employed in this study primarily serves to ascertain the significance levels of various criteria, demonstrating its effectiveness as a decision-making tool in crop selection when the right set of criteria is applied.